ANALISIS NILAI TAMBAH INFORMASI LAPORAN ARUS KAS - Zaki Baridwan (Journal of Indonesian Economy and Business (JIEB), 1997)
The Indonesian Institute of Accountants published the Statement ofFinancial Accounting Standards No.Z "Cash Flow Statement" requires companies to publish the Cash Flow Statement starts in 1994. Similar requirement has also been required by the Financial Accounting Standards Board of the USA in 1989. The required Cash Flow Statement contains cash flow information, separated into Total Cash Flow, Cash Flow From Operations, Cash Flow From Investing Activities, and Cash Flow From Financing Activities. The financial statements issued periodically by companies now consist of a balance sheet, an incomestatement, a statement of retained earnings, and a cash flow statementCash Flow Statement could be prepared based on two differentapproaches, direct and indirect methods. The indirect method of preparing cash flow statement is performed by adjusting profit or loss amount in the income statement bynoncash transactions, investment and financing activities. By using this method, therefore, cash flow information logically will have relationships with income statement information, at least cash flow from operation with incomefrom operation. The problem is, publication of cash flow statement is expected to add value to the users of financial statements. If the new information is related to information that is already provided by the income statement, then, the objectives of issuing cash Sow statement would not be achieved. This study evaluates relationships and similarity of the two information (Le. income statement and cash Sow) using data from 62 public manufacturing companies. The results of conelation and Wilcoxon Signed Rank tests show that income statements information is highly conelated but do have significant differences with cash Bow information. Therefore, the conclusion is that there is additional value mat is obtained by users of financial statements. The accounting authority has conectly requires the publication of cash flow statement.